Analytical study on Himalayan research outcomes: Special reference to Scopus indexed publications - Srinivasaragavan, S.; Gayathri, S.; Varsha, V.K.; Jaya Suriya Dheva, R.S. (University of Jaffna, 2022)
The Himalayas are new fold mountains along India’s northern boundary. The Himalayan range is one of the world’s tallest and roughest mountain ranges. The study’s main purpose is to conduct an analytical study on the Himalayan Research Outcomes published in the Scopus database. It also aims to determine the year-wise productivity of Himalayan research, identify and measure the research literature output in Himalayan Research, and find the most productive authors and author productivity patterns in Himalayan Research. The data considered for the study was from 1989-2021 in the Scopus database. Fourteen thousand three hundred seventy-five records were found in the predefined study period, out of which 1879 journals contributed to “Himalayas”, which were examined for the study. The study found that in the year 2020, the publications were highest. The “Journal of Asian Earth Sciences” has published the highest number of articles. Among the top insti tutions, “The Chinese Academy of Sciences” ranked at the top of the list. It was also found that India had the highest share of publications. The outcome of the present research study added value to the existing scientometric literature and acted as a source to guide the researchers on Himalayan Studies. The outcome also enabled the libraries and policymakers to know the scholarly information resources, the institutions, and the leading scientists engaged in Himalayan mountains research and related subjects to organize the knowledge resources.
Keywords: Himalayan research; Himalayan studies; Scientometrics; Author productivity